Rancang Bangun Sistem Informasi Surat Pengaduan Kerusakan IT Berbasis Web (Studi Kasus Unit SIM RSI Surabaya A Yani) - Ilham Fakhri Huda; Muh Nur Luthfi Aziz (Journal Of Informatics And Busisnes, 2024)
The advancement of technology necessitates the IT unit to have an efficient mechanism for reporting discrepancies needed in the work environment. This research aims to design and develop a web-based Information System for IT Damage Complaints as a reporting medium that enhances transparency, accessibility, and effectiveness in managing and tracking necessary repairs for RSI Surabaya A Yani. The system development methodology used is the Waterfall model, involving stages such as needs analysis, system design, code programming, testing, and maintenance. Integrated features include the recording of damage complaint letters, monitoring repair status, managing repair history, and evaluating the effectiveness of repairs. Additionally, the system is equipped with an automated notification mechanism to inform stakeholders about the progress of repairs. The results of the system testing indicate that the implementation of this web-based IT Damage Complaint System facilitates the reporting process more efficiently and enhances information accessibility related to system repairs at RSI Surabaya A Yani. This is based on survey results filled out by system Users, showing values ranging from 81.33% to 91.33% with an indicator of excellent. This research provides practical contributions to improving web-based IT damage complaint management. The implications of this study can assist the IT unit in managing the reporting and repair processes effectively.